2021
DOI: 10.3390/su13063513
|View full text |Cite
|
Sign up to set email alerts
|

Production of High Added-Value Chemicals in Basfia succiniciproducens: Role of Medium Composition

Abstract: Succinic acid production through biological fermentation led to new pathways in the integration of renewable feedstock from different industries into biosynthesis. In this article, we investigate the population growth dynamics and succinic acid production potential of the recently isolated natural succinic acid producer, Basfia succiniciproducens, using in silico constraint-based metabolic models as well as in vitro experiments. Our work focuses on the influence of different renewable substrates and added yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 45 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…YE and carbon source significantly affected the SA and LA production. 3,33 It was found that B. succiniciproducens cultured in medium with glucose as a carbon source produced higher SA and other acids than medium with xylose and glycerol. However, LA was barely produced in the case of glycerol, and FA was not found in the case of xylose.…”
Section: 3mentioning
confidence: 99%
See 4 more Smart Citations
“…YE and carbon source significantly affected the SA and LA production. 3,33 It was found that B. succiniciproducens cultured in medium with glucose as a carbon source produced higher SA and other acids than medium with xylose and glycerol. However, LA was barely produced in the case of glycerol, and FA was not found in the case of xylose.…”
Section: 3mentioning
confidence: 99%
“…However, LA was barely produced in the case of glycerol, and FA was not found in the case of xylose. 3 A cheap substrate from industrial wastewater could be an alternative source for SA with low levels of unwanted acids.…”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations